Family murder, violence and the South African psyche - Harper, Eric; Tomlinson, Marie (PINS-Psychology in Society, 2026)
"A primary group of this kind is a number of individuals who have put one and the same object in the place of their ego ideal and have consequently identified themselves with one another in their ego." (Freud S, 1921, Being in love and hypnosis, in Group Psychology). On June 17, the Grobler family of Jeffrey's Bay were watching television. Mr Petrus Grobler (29) answered the telephone only to be informed that he had lost an important building contract. He went through to the lounge, told his wife and two sons to say goodbye - they kissed, following which he killed the three of them with a shotgun. He then attempted suicide himself. He said, "his family meant everything to him". What began in 1983 as a relatively isolated phenomenon, with around ten people being involved, has increased with such dramatic rapidity that around sixty people died as a result of family murder in 1987, while around twenty died in 1988. The fact that it is virtually an unheard of phenomenon overseas and the fact that over 80% of all family murders are committed by Afrikaans speaking white South Africans, has necessitated that serious investigations into causal factors be undertaken. The aim of this paper will be to outline the psychodynamic factors which make this phenomenon such a uniquely South African one. In using a psychodynamic approach we hope to avoid reproducing yet another "over socialised conception of humans" (Wrong, in Bocock, 1983). We hope to provide the reader with a psychodynamic understanding of family dynamics within the South African context.